MENGUAK AGENDA KOLONIAL DALAM PERINTAH PEMBANTAIAN ULANGAN 7:1-11 - Owen Brian Kawengian (DA'AT : Jurnal Teologi Kristen, 2025)
It is undeniable that the Old Testament in the Christian Bible contains the extremely violent narratives such as slaughter and genocide. One of them is Deuteronomy 7:1-11, which has been the subject of discussion and debate for a long time among scholars because of the nature of the narrative, which contradicts the image of a merciful God in Christian faith. More terribly, the text, and other similar texts, had been used to legitimize colonization and genocide of native people by European colonizers in the 18th-19th centuries. As a text that has been studied and discussed frequently, research on the extermination command in Deuteronomy 7 has often been carried out. However, what differentiates this article from another is the use of a postcolonial criticism that scrutinizes the agenda of colonialism not only in the narrative within the text but also in the text's production process. As a result, this article offers two important key points as an alternative way to interpret the narrative of the massacre command in the text.